Maternal and Neonatal Serum Zinc Level and Its Relationship with Neural Tube Defects (Journal of Health, Population and Nutrition, 2010)
Neural tube defect (NTD) is a multi-factorial disorder in which nutritional, genetic and environmental factors are involved. Among the nutritional factors, low level of serum zinc has been reported from different parts of the world. This hospital-based case-control study was conducted with the objective of finding the relationship between serum zinc level in newborns and their mothers and NTDs in a Bangladeshi population. The study was conducted during August 2006-July 2007 at the Bangabandhu Sheikh Mujib Medical University (BSMMU) in Dhaka. In total, 32 mothers and their newborns with NTDs were included as cases and another 32 mothers with their normal babies were included as controls. Concentration of serum zinc was determined by pyro-coated graphite furnace atomic absorption spectrophotometer (GF-AAS). The mean age of the case and control mothers was 25.28 years and 24.34 years respectively. The mean gestational age of the case newborns was 36.59 weeks and that of the control newborns was 37.75 weeks. The mean serum zinc level of the case and control mothers was 610.2 μg/L and 883.0 μg/L respectively (p